2008
DOI: 10.1007/s00701-008-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome of anterior cervical discectomy and fusion using coral grafts

Abstract: Despite satisfactory clinical results and a long follow-up period, coral implants yield low fusion rates, particularly in patients with discal hernia of two-level arthrodesis. The use of coral grafts cannot be recommended when fusion is one of the post-operative endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Twenty-five studies [20,2325,33,35,36,40,47,51,59,61,62,68,69,7376,78,85,86,91,117,118] containing 142 patients with infection of 3489 patients after cervical surgery were included. Figure 21 shows that the incidence was 2.8% (95% CI 1.7%–4.0%), with substantial heterogeneity of incidence observed.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies [20,2325,33,35,36,40,47,51,59,61,62,68,69,7376,78,85,86,91,117,118] containing 142 patients with infection of 3489 patients after cervical surgery were included. Figure 21 shows that the incidence was 2.8% (95% CI 1.7%–4.0%), with substantial heterogeneity of incidence observed.…”
Section: Resultsmentioning
confidence: 99%
“…In 38 of the 146 articles, it was mentioned whether the radiographs were analysed by a radiologist or a clinician. In 26 of these, analysis was performed by a radiologist [10,13,20,24,32,49,50,54,57,58,64,74,85,94,[97][98][99][100][101][102][103][104][105][106][107][108]. They found fusion was achieved in 93.5% of patients after a median follow-up of 23 months.…”
Section: Methods Of Measuring Bony Fusionmentioning
confidence: 99%
“…67 Clinical studies utilizing Biocoral ® have shown mixed results. [74][75][76][77][78][79][80][81][82][83] Early studies have utilized Biocoral ® in the treatment of bony maxillofacial defects. Of interest is the study of Roux et al presented the outcome of this product in 183 patients.…”
Section: Animal Studiesmentioning
confidence: 99%
“…75 In cervical fusion a poor fusion rate of 45 % and 60% has been reported in two studies of 48 and 40 patients. 76,77 In scaphoid fractures, the utilization of a composite graft composed of Biocoral ® , BMP and collagen resulted in a high failure rate of 80%. 78 The use of the same implant however, in 4 diaphyseal and one olecranon ulnar non-union resulted in successful consolidation in all cases.…”
Section: Animal Studiesmentioning
confidence: 99%